Dynamicizing the Discourse of Hadith: Study of HR. Bukhārī No. 1291 and Abū Dāwūd No. 4291 from a Philosophical Hermeneutics Perspective - Rukmana, Fachruli Isra; Hidayat, Aldi; Nazahah Najiyah, Nur Laili Nabilah; Abdul Hamid, Mohammad Fahmi; Yuzar, Sri Kurniati (An-Nida', 2024)
Hadith studies have experienced stagnation compared to Qur’anic studies, which continue to develop with various new ideas. This stagnation is caused by the dominance of sanad analysis, debates over the status of hadith as a secondary source in Islam, and the use of certain hadiths to reject reform. One of the hadiths often cited to oppose renewal is the prohibition against lying about the Prophet Muhammad, as narrated by al-Bukhārī. This study aims to re-examine the hadith prohibiting fabricating statements about the Prophet and the hadith on renewal (tajdīd) using the philosophical hermeneutics of Hans-Georg Gadamer. This approach emphasizes the concepts of fusion of horizons and effective historical consciousness to revitalize hadith studies in the modern context. This research employs a qualitative method with a library research approach. The analysis focuses on two key hadiths: the prohibition against lying about the Prophet Muhammad (HR. al-Bukhārī No. 1291) and the hadith on tajdīd (HR. Abū Dāwūd No. 4291). The study presents two main conclusions. First, the stagnation in hadith studies results from rigid traditionalism, where hadith is primarily treated as a theological doctrine rather than an epistemological paradigm. Second, classical and modern hadith sciences have yet to fully ensure the authenticity of hadith texts exactly as intended by the Prophet. However, the prohibition against fabricating hadith implicitly demands the purification of hadith from additional narrators’ insertions. Thus, this article proposes originalization as an implicit message of HR. al-Bukhārī and an application of the tajdīd hadith from Abū Dāwūd. Originalization is expected to open new discussions in hadith studies, such as hadith revisionism, the phenomenology of memory, and the archaeology and anthropology of narrators.Abstrak: Studi hadis mengalami stagnasi jika dibandingkan dengan studi Al-Qur’an yang terus berkembang dengan berbagai gagasan baru. Stagnasi ini disebabkan oleh dominasi kajian sanad, perdebatan mengenai kedudukan hadis sebagai sumber sekunder dalam Islam, serta penggunaan hadis tertentu untuk menolak pembaruan. Salah satu hadis yang sering dijadikan dasar untuk menolak pembaruan adalah larangan berbohong atas nama Nabi Muhammad, sebagaimana diriwayatkan oleh al-Bukhārī. Penelitian ini bertujuan untuk menelaah kembali hadis larangan berdusta atas nama Nabi dan hadis tentang pembaruan (tajdīd) dengan menggunakan perspektif hermeneutika filosofis Hans-Georg Gadamer. Pendekatan ini menekankan konsep fusion of horizons (penggabungan cakrawala) dan effective historical consciousness (kesadaran historis yang efektif) untuk mendinamisasi kajian hadis dalam konteks modern. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan. Analisis dilakukan terhadap dua hadis utama: larangan berdusta atas nama Nabi Muhammad (HR. al-Bukhārī No. 1291) dan hadis tentang tajdīd (HR. Abū Dāwūd No. 4291). Penelitian ini menghasilkan dua kesimpulan utama: Pertama, stagnasi kajian hadis disebabkan tradisionalisme yang kaku dan cenderung selalu digunakan sebagai doktrin teologis bukan sebagai paradigma epistemologi. Kedua, ilmu hadis klasik dan modern belum mampu menjamin keaslian matan sepersis yang dikehendaki Nabi padahal larangan memalsukan hadis secara tersirat menuntut sterilisasi hadis dari redaksi tambahan perawi. Karena itu, artikel ini mengajukan orisinalisasi sebagai panggilan tersirat HR. Bukhari sekaligus pengamalan atas hadis tajdīd riwayat Abū Dāwūd. Orisinalisasi nantinya akan membuka wacana baru hadis, seperti revisionism hadis, fenomenologi ingatan, arkeologi dan antropologi perawi, dan lain-lain.